Design and Control Strategy for a Solar -Powered Autonomous Underwater Vehicle with an Unconventional Shape - Yu Chunliang; Chen Yuxiang; Zhu Hong; Xiong Hong; Lunyang Lin; Xing Yiyang; Zheng Guodong (Polish Maritime Research)
Solar-powered autonomous underwater vehicles (SAUVs) can harness sustainable natural energy, meaning that they are capable of providing long-term mission support. This paper describes ongoing development work on the overall design of a SAUV. It outlines the design goals for the vehicle, with a particular focus on the unconventional shape resulting from the integration of solar panels within the body of the SAUV. It is equipped with an array of commonly used sensors as its perception system, thus ensuring comprehensive environmental awareness. Due to its unique negative lift shape and its reliance on a single vector thruster for propulsion, the difficulty of motion control of this SAUV is significantly increased. In response to this aspect, and based on practical considerations, this paper proposes a control strategy that divides the vector thrust into three major control forces: thrust () for regulating speed; thrust () for changing the heading, and thrust () for controlling depth. To address the varying levels of difficulty presented by speed control, heading control, and depth control, differentiated control methods are designed based on Proportional-Integral-Derivative (PID) and active disturbance rejection control (ADRC) algorithms, respectively. Through a series of experiments in a water tank, the validity and applicability of the proposed algorithms are verified for practical applications.